A NEW NATURAL HYBRID OF NEPENTHES FROM MT. KINABALU ( SABAH ) - Adam, Jummat H.; Wilcock, C.C (REINWARDTIA, 1992)
A new natural hybrid of Nepenthes, N. x alisaputraiana, from Mt. Kina-balu Sabah is described.